Study on the comprehensive evaluation of TCM service capacity in 71 county-level TCM hospitals of Zhejiang Province in China - Xuehui Meng; Xiaoyue Xiao; Jason Li; Tong Pei; Xinhao Lin; Dan Wu (KeAi Communications Co., Ltd., 2024)
Objectives: This study constructed an evaluation index system of Traditional Chinese Medicine (TCM) service capacity of county-level TCM hospitals, investigated the status quo of TCM service capacity of county-level TCM hospitals in Zhejiang Province, aiming to provide suggestions and references for the high-quality development of TCM hospitals in China. Methods: Delphi expert consultation method and analytic hierarchy process were used to construct the comprehensive evaluation index system and its weight. Field investigation method was used to conduct a cross-sectional survey of 71 county-level TCM hospitals in Zhejiang Province, to calculate the scores of each index, and to compare the service capacity of county-level TCM hospitals. Results: The evaluation index system includes 6 first-level indicators, 15 ​second-level indicators and 42 third-level indicators. The average score of service capacity of 71 county-level TCM hospitals was 60.73 points, among which the highest score was 80.72 points, and the lowest score was only 33.52 points. There are great differences in TCM service capacity among hospitals. Conclusions: We have come to the conclusions that the index system can evaluate the service capacity of TCM hospitals effectively. In addition, there are still problems in the development of county-level TCM hospitals in Zhejiang Province, such as insufficient service capacity, great gap of development between regions, and inadequate development of characteristic advantages of TCM. Thus, it is necessary to consolidate the development foundation, pay more attention to the balance of regional development, and improve the service capacity of county-level TCM hospitals.